2012
DOI: 10.4103/0973-8258.102825
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction: A review and herbs used for its treatment

Abstract: Erectile dysfunction (ED) or male impotence is defined as the inability to have or sustain an erection long enough to have a meaningful sexual intercourse. ED tends to occur gradually until the night time or early morning erections cease altogether or are so flaccid that successful intercourse does not occur. Sexual health is an important determinant of quality of life. Today, millions of men, young and old, suffer from ED due to high levels of synthetic hormones (known as Xenoestrogens) in our diet/environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…The use of PDE-5 inhibitors such as sildenafil, tadalafil and verdanafil does not only raise the levels of cGMP (Chuang et al 1998;Corbin 2004) but also stimulates activation of cGMP and increases NO bioavailability for the relaxation of penile tissue that results in penile erection. However, these inhibitors also elicit several side effects, including headache, dyspepsia, nasal congestion, visual abnormalities among others (Saxena et al 2012). The result revealed that PDE-5 activity was inhibited by the extracts concentration dependently.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The use of PDE-5 inhibitors such as sildenafil, tadalafil and verdanafil does not only raise the levels of cGMP (Chuang et al 1998;Corbin 2004) but also stimulates activation of cGMP and increases NO bioavailability for the relaxation of penile tissue that results in penile erection. However, these inhibitors also elicit several side effects, including headache, dyspepsia, nasal congestion, visual abnormalities among others (Saxena et al 2012). The result revealed that PDE-5 activity was inhibited by the extracts concentration dependently.…”
Section: Discussionmentioning
confidence: 60%
“…This has motivated a continuous search for herbal/medicinal plant with erectogenic potentials as there are less side effects associated with herbal medications (Saxena et al 2012;Oboh et al 2015;Akomolafe et al 2016). Plantain [Musa sapientum Linn.…”
Section: Introductionmentioning
confidence: 99%
“…Several oral inhibitors of PDE‐5 such as sildenafil citrate and verdanafil have been formulated; however, these inhibitors come with their attendant side effects which include headache, nasal congestion, visual abnormalities, etc. (Saxena, Prakash, Porwal, Sissodia, & Sharma, ). This called for the search for alternative natural therapies with minimal or no side effects.…”
Section: Resultsmentioning
confidence: 99%
“…The use of PDE‐5 inhibitors do not only raise the levels of cGMP but also increase NO bioavailability for the relaxation of penile tissue (Corbin, ). Although, the use of synthetic inhibitors such as sildenafil, has been proven to be effective, however, reports have shown that they also elicit some complications (Herrmann, Chang, Klugherz, & Mahoney, ; Saxena, Prakash, Porwal, Sissodia, & Sharma, ). Hence, the use of plant‐base food/materials is greatly encouraged to combat ED (Gupta et al, ; Adefegha, Oboh, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although, the use of synthetic inhibitors such as sildenafil, has been proven to be effective, however, reports have shown that they also elicit some complications (Herrmann, Chang, Klugherz, & Mahoney, 2000;Saxena, Prakash, Porwal, Sissodia, & Sharma, 2012). Hence, the use of plant-base food/materials is greatly encouraged to combat ED (Gupta et al, 2005;Adefegha, Oboh, et al, 2016 with the studies of Kotirum, Ismail, and Chaiyakunapruk (2015) and Adefegha, Oyeleye, Dada, et al (2018) that plant food, especially those that are rich in phenolic compound, could inhibit PDE-5 activity, and can be employed in the management of ED.…”
Section: Re Sults and Discussionmentioning
confidence: 99%